Survival of the dysplastic hip after periacetabular osteotomy: a meta-analysis. Issue 2 (March 2023) - Ahmad, Sufian S; Giebel, Gregor M; Perka, Carsten; Meller, Sebastian; Pumberger, Matthias; Hardt, Sebastian; Stöckle, Ulrich; Konrads, Christian
Background: Periacetabular osteotomy (PAO) has become a popular procedure for re-orientation of the acetabulum in patients with a developmental pathomorphology. Since its first description by Reinhold Ganz in 1988, many institutions worldwide have adopted the procedure for the treatment of developmental hip dysplasia (DDH) and have subsequently reported their results. The aim of this study was to provide a meta-analysis of the likelihood of long-term survival of a dysplastic hip after PAO. Methods: A systematic literature review was conducted using Medline, Cochrane and "Web of Science" databases to identify articles reporting survival estimates for PAO in patients with DDH. To be included in the analysis, studies had to include patient cohorts aged <40 years, with Osteoarthritis grade < Tönnis III and no form of neuromuscular dysplasia. Adjustment for cohort overlap was performed. Quality assessment included level of evidence (LOE) according to the oxford center for LOE criteria and the "Methodological index for non-randomized studies (MINORS)". After data extraction, a random-effects meta-analytical model was applied to provide weighted mean estimates of survival at 5 years, 10 years, 15 years and 20 years. Results: Nine relevant articles included 2268 dysplastic hips that underwent PAO in 9 institutions. Of the included studies, 5 presented level III evidence and 4 presented level IV evidence. The MINORS score was 11 for 3 studies, 12 for 4 studies and 13 for 2 studies. The 5-year survival after PAO was 96.1% (95% CI, 94.9–97.3), the 10-year survival was 91.3% (95% CI, 87.7–94.8), 15-year survival 85.0% (95% CI, 78.9–91.1), 20-year survival 67.6% (95% CI, 53.9–81.3). Conclusions: The results provide a representative survival estimate of a dysplastic hip after PAO based on global evidence. This should provide clinicians and patients with an adequate reflection of prognostic expectations after this kind of surgery.